Structure of Patients with Hepatocellular Cancer (Data Analysis from Two Specialised Centres) - M. V. Mayevskaya; M. S. Novruzbekov; I. M. Borovkov; D. G. Trofimova; M. S. Zharkova; V. D. Lunkov; K. N. Lutsyk; O. D. Olisov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To identify trends in the structure of patients with liver diseases, in particular hepatocellular cancer (HCC), by analysing the experience of two specialised medical centres.Materials and methods. A retrospective analysis of the medical records of hepatological patients who sought medical treatment at to the V.Kh. Vasilenko Clinic of Propaedeutics of Internal Diseases, Gastroenterology and Hepatology of the Sechenov University in 2013, 2014 and 2017 (total 2459 patients) was carried out. The number of patients with chronic viral hepatitis (CVH) was 651, with non-alcoholic fatty liver disease (NAFLD) — 590, with alcoholic liver disease (ALD) — 66, with autoimmune liver diseases — 416, with liver cirrhosis (LC) of any etiology 407, other liver diseases — 329. A retrospective analysis of the medical records of patients with HCC who were examined and treated at the N.V. Sklifosovsky Research Institute for Emergency Medicine in the period from 2008 to 2017 (n = 86) was carried out.Results. The ratio of patients with chronic hepatitis C and B in 2013–2017 significantly changed. An almost twofold decrease in the number of patients with chronic hepatitis C (210 patients in 2013 and 141 patients in 2017) and an increase in the number of patients with chronic hepatitis B (20 patients in 2013 and 45 patients in 2017) was observed. An almost twofold increase in the total number of NAFLD patients was detected (163 patients in 2013 and 276 patients in 2017). The number of ALD patients increased from 12 patients in 2013 to 31 patients in 2017. The proportion of patients with autoimmune liver diseases in the overall structure of patients who applied to the department was 20 % in 2013, 13.6 % in 2014 and 10.8 % in 2017. An almost twofold decrease in the number of patients with alcoholic LC and LC associated with HBV was observed (73 patients and 17 patients in 2013 and 38 patients and 6 patients in 2017, respectively) as well as a noticeable increase in the number of patients with alcoholic LC and LC associated with HCV (6 patients and 51 patients in 2013 and 26 patients and 75 patients in 2017, respectively). In the analysis of HCC patients, the ratio of men to women was 3:1 (64 men and 22 women), the median age was 54.5 years (IQR 48–59). The median time from the establishment of chronic liver disease to the detection of HCC was 7.5 years (IQR 3–14.5). In 86 % of cases, the HCC development was preceded by cirrhosis (Child-Pugh A: n = 24; Child-Pugh B: n = 30; Child-Pugh C: n = 20), in 14 % — by chronic hepatitis. Viral liver lesions were the leading cause of HCC in 79 % (n = 68), ALD in 4 % (n = 3), NAFLD in 1 % (n = 1), AIH in 1 % (n = 1). In 10 % (n = 9), a combined liver lesion was observed, in 5 % (n = 4), no previous liver disease was known. The highest five-year survival rate (100 %) was found in the group of patients who received antiviral therapy (AVT) before and after liver transplantation.Conclusions. NAFLD, ALD, and chronic hepatitis B patients began to seek medical help more frequently. An increase in the number of patients with autoimmune LC and LC associated with chronic hepatitis C virus (HCV) infection was observed. The conducted analysis of trends in the structure of HCC patients showed that chronic HCV and HBV infection is the main prerequisite for the development of cancer. Liver transplantation is the most effective treatment for HCC. AVT before and after liver transplantation allows a statistically significant increase in the five-year posttransplant survival of HCC patients with chronic hepatitis C to be achieved.